(untitled) (Faridpur Medical College Journal, 2011)
Improvement of maternal health care services is regarded as an important component for achieving targets of MDGs by the year 2015. A cross-sectional community based study was carried out to find out the status and utilization of maternal health care services in Pangsa Upazilla of Rajbari District among 517 mothers who had at least one child up to 1 year of age. The study was conducted from June to August in the year 2008. Data were collected through face-to-face interview using purposive sampling technique. Most of the respondents were in the age group of 20-29 years (69.05%) and 35.01% of them had received primary education. Sixty seven percent of them had average monthly income of Taka 3001-5000. Eighty percent of the respondents were at the age group of 15-19 years when they got married. Most of the mothers (71.57%) got antenatal care during their last pregnancy and more than 80% of them had completed their TT vaccination schedule during pregnancy period. More than 80% of the deliveries were taken place at home. Eighty five percent of the deliveries were normal delivery and most of them (77.76%) were attended by the untrained traditional birth attendants (TBA). Hemorrhage was found to be the highest reported obstetric complication (37.50%). This study offered a picture of the maternal health care services in rural Bangladesh and detected the need for future work in this area. Key words: Maternal health care service; ante-natal care; delivery; rural area; Bangladesh DOI: 10.3329/fmcj.v5i1.6808 Faridpur Med. Coll. J. 2010;5(1):17-20